From Journalism Studies to Journalism Theory - Machado, Elias (Brazilian journalism research, 2005)
This paper comprises three parts –- 1) recognition of professional practice as a legitimate object of research; 2) development of methodologies that are adjusted to the particularities of the area; and 3) funding of multidisciplinary experiments on applied research. My intention here is to build on the mapping of existing studies to discuss some assumptions and to consolidate journalism as a ﬁ eld of knowledge, based on the distinction between journalism studies and journalism theories.